UPAYA MENINGKATKAN INDEKS PROFESIONALITAS KINERJA ASN DALAM MENDUKUNG REFORMASI BIROKRASI - S.Pd, M.Pd Zul Pahmi (Jurnal Widya, 2025)
The State Civil Apparatus (ASN) is a key element with a strategic role in the administration of government and public services. To achieve good governance, ASN are required to be professional, competent, and possess integrity. The success of bureaucratic reform is largely determined by the level of ASN professionalism in carrying out their duties and functions. The Indonesian government has established the ASN Professionalism Index as an instrument to measure ASN quality based on the dimensions of qualifications, competence, performance, and discipline. However, the results of this index indicate that ASN professionalism in various government agencies remains suboptimal. One instrument for measuring ASN quality is the ASN Professionalism Index. However, in practice, this index still shows suboptimal results in various government agencies. This study aims to analyze various efforts that can be made to improve the ASN Professionalism Index to support the realization of good governance. The research method used is a literature study with a descriptive-qualitative approach through a review of laws and regulations, government policy documents, and relevant scientific publications.The study results indicate that improving the Civil Servant Professionalism Index requires a comprehensive and sustainable approach through competency development, optimizing the performance appraisal system, implementing a merit system, strengthening discipline and integrity, and fostering a leadership role in building a professional work culture. Consistent implementation of these efforts is expected to improve the quality of civil servants and public services. Keywords: Civil Servants, Professionalism, Performance, Professionalism Index, Bureaucratic Reform.